The direct thrombin inhibitor argatroban effectively prevents cardiac catheter thrombosis in vitro - Raaz, Uwe; Kaeberich, Anja; Maegdefessel, Lars; Buerke, Michael; Busshardt, Marese; Schubert, Sebastian; Russ, Martin; Plehn, Alexander; Ebelt, Henning; Werdan, Karl; Schlitt, Axel (Thrombosis and Haemostasis, 2010)
The direct thrombin inhibitor argatroban offers some significant advantages over unfractionated heparin (UFH) and is recommended as an alternative anticoagulant during percutaneous coronary interventions (PCI). The impact of argatroban on cardiac catheter thrombosis – a severe potential complication of PCI – has not been systematically studied yet. The aim of the present study was to test in vitro the hypothesis that argatroban is equivalent to the more established anticoagulants UFH and enoxaparin in preventing catheter thrombus formation. Blood pretreated with the anticoagulants of interest was continuously circulated through a guiding catheter by using a roller pump for a maximum experimental period of 60 minutes. In an alternate model, coagulation was mechanically induced by a magnetic stirrer. Coagulation parameters, overall thrombus weight and electron microscopic features (deposits of platelets and fibrin on the catheter surface) were quantified as endpoints. Argatroban (administered as bolus or continuous in-fusion), UFH (bolus), and enoxaparin (bolus) significantly reduced catheter thrombus formation compared to untreated controls. Here, neither overall thrombus weight nor platelet/fibrin deposition was different among the specific anticoagulants. Declining ACT (activated clotting time) levels – which were found in the argatroban bolus group – could be prevented by continuous infusion. In magnetic stirrer-induced coagulation, thrombus weight was lower following bolus treatment with UFH and enoxaparin compared to argatroban. These data suggest that the potential for argatroban in preventing catheter thrombosis is comparable to that of UFH and enoxaparin. However, the anticoagula-tory efficacy varied, depending on the model of coagulation activation, which demonstrates the necessity for specific testing.
Keywords: Anticoagulation; direct thrombin inhibitors; PCI